Correlation Between Acute Phase Delta NIHSS and Quality of Life Score in Post Thrombotic Infarct Stroke Patient in Dr. Moewardi General Hospital via Tele-Stroke Specific Quality of Life-12 Questionnaire (SSQOL-12) - Tedjo, Raden Andi Ario; Savitri, Martha Oktavia Dewi; Putra, Stefanus Erdana (Faculty of Medicine Universitas Sebelas Maret, 2023)
Introduction: Stroke is one of the most common diseases causing disability. Stroke severity assessed using National Institute Health Stroke Scale (NIHSS) was recognized affecting quality of life in stroke patients. This study evaluated the NIHSS delta as a predictor of quality of life in thrombotic stroke patientsMethods: This study was conducted from January to September 2022 with cross-sectional approach. At inpatient setting, NIHSS was assessed at admission, first 24 hours, and discharge. Patient’s quality of life was evaluated using the SSQOL-12 questionnaire via telephone. Bivariate linear regression analysis was used to assess this correlation.Results: Demographic data of 61 patients showed that 65.4% of patients were male, 54.1% of patients aged <60 years, and 67.2% had moderate stroke (NIHSS 6-15). The results of bivariate analysis using linear regression showed that both the 24 hour-delta NIHSS and the delta NIHSS-admission-discharge were positively related to SSQOL-12 score (p = 0.000).Conclusion: Delta NIHSS can be used as clinical improvement predictor with positive correlation to the quality of life in thrombotic stroke patients